DELINIASI DAS BERBASIS SISTEM INFORMASI GEOGRAFIS DALAM RANGKA MENDUKUNG PENGELOLAAN DAS TERPADU (Studi Kasus : DAS Manjuto Provinsi Bengkulu-Indonesia) - Gusta Gunawan (Universitas Bengkulu, 2019)
Improper management of land-use activities cause the disruption of bio-physical balance in the watershed, resulting in flooding, drought, sedimentation, etcetera. This led to many losses, both in economic and environmental. To reduce the impacts, implementation of integrated and sustainable watershed management is urgently required. This requires efficient and effective implementing agencies. They should have the similar perception regarding their respective authority in managing the watershed. To avoid conflict of interests among the agencies concerned, determining the boundaries and area of watershed based on bio-physical parameters is absolutely indispensable. The purpose of the study is to delineate the boundary and determine the area of Manjuto watershed in Bengkulu Province, Indonesia. The 4-step procedure is applied, comprises DEM conditioning, flow routing, delineation of watershed boundary and determination of watershed area. Extensive calculations performed by considering the topography of the region. The test using transectlines elevation proved that the result is accurate and consistent with the the oretical definition. Afterward, the result is compared to the existing information. The result shows that Manjunto watershed area is 79,581 hectares or 7.4% smaller than the area defined by the Ministry of Public Work and 29.3% largerthan the area defined by the Ministry of Forestry.